Pandemics and interdisciplinarity: A new look at education (Research, Society and Development, 2021)
The purpose of this article is to verify the impact of the Covid-19 pandemic to rethink education based on the concepts of interdisciplinarity, since in 2020 humanity was surprised by the new Coronavirus pandemic, victimizing millions of people worldwide, which caused changes in the current educational model. To develop this article, we did qualitative research. So, we made we analyzed data from a survey conducted by the Brazilian Association of Distance Education (ABED) on remote classes in basic education and we conducted a semi-structured interview with the principal of a school located in Luziânia-GO, in order to verify whether, despite the challenges imposed by the pandemic, it was possible to develop, in an interdisciplinary way, the pedagogical activities in the school. Researches show that the change from classroom to remote teaching was an imperative that demanded, in many cases, a change in the behavior of teachers, students, institution and guardians. Therefore, in this context, a new way of thinking about education emerged, arising from the needs of the moment that include the development of society and the importance of working with planetary issues, in which interdisciplinarity is present as eco-training, impacting pedagogical practice, aiming to make students rethink their reality, but to do this within a world context.